Production risk analysis for organic cabbage farming in Semarang district, Central Java - Rahmawati, Nur; Yogatama, Candra; Winahyu, Wulansari; Kasim, Anisah (2023)
There is some risk and uncertainty involved with purchasing organic cabbage. Farming is highly susceptible to natural phenomena such as high rainfall and pest infestations. It will have consequences for the development of the harvested area, and fluctuations in production can indicate a risk to agricultural production. This study aims to determine the factors that influence organic cabbage production and to determine the factors that affect the risk of organic cabbage production in Getasan District. The Semarang Regency, where this study was conducted, is the largest cabbage market. A total of 73 farmers were selected using a census-based sample from four INOFICE-certified organic farmer groups: Batur Village, Wates Village, Tajuk Village, and Kopeng Village. The analysis method utilized the Just and Pope production risk function and the Cobb-Douglass type production function. The Cobb-Douglass production function analysis revealed that land area, seeds, manure, and cropping patterns all positively and substantially affected organic cabbage production, but only to a limited extent. According to the Just and Pope production risk function, the risk associated with farming organic cabbage could be mitigated by increasing land area and diversity in cropping patterns.